METHODOLOGY OF INTERPRETATION WITH STRUCTURALISM APPROACH IN ADAM PROPHET'S STORY - Dewi, Kartini Kusuma (Journal of Islam and Science, 2019)
Structuralism approach is one of the many interpretive research methodologies, because this approach uses the philosophy of structuralism with many theories. This approach as an analytical lens for developing interpretation sciences etc. In this paper, the interpretation of structuralism approach in the interpretation of Muhammad Abduh and Rasyid Ridha will be explained. Muhammad Abduh and Rasyid Ridha are modernist-contemporary thinkers who are very influential in the field of interpretation. In this structural analysis, they argue in interpreting verses using the approach of structuralism in the interpretation of verses of the story of the Prophet Adam. This approach is a formalist analysis model that tends to follow the chronological rules of the story structure of successive events.